(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Principles and factors promoting the formation of specialized zones of gardening, in the article are discussed in the article, as well as opportunities for fruit and grape raising in agricultural zones. Rational distribution of gardening on the slopes and valleys and its social-economic and ecological significance are grounded in the article.